Microstructural evolution and mechanical performance of friction stir spot welded ultrafine carbide-free bainitic steel: Role of dwell time - Maryam Kabirmohammadi; Sasan Yazdani; Tohid Saeid; Majid Pouranvari (Journal of Materials Research and Technology)
This study focuses on unraveling the role of dwell time on microstructural evolution, mechanical performance, and failure characteristics of friction stir spot welded ultrafine carbide-free bainitic steel. Results clarify that the microstructures of the different weld zones exhibit a receptive behavior to extended dwell time, by which not only coarser martensite is acquired within the stir zone (SZ), thermo-mechanically affected zone (TMAZ), and fine-grain heat affected zone (FGHAZ) but also sub-critical heat affected zone (SCHAZ) experiences a more pronounced tempering. Applying a dwell time of 3 s is sufficient to make an ample bonding width containing refined martensite, being effective in retarding the crack propagation, and in turn, delivering a joint with the highest load-bearing capacity. However, enlarging the bonding width at dwell times beyond 3 s fails to provide higher peak loads owing to the formation of coarse martensite within the SZ. The failure modes of the welds are classified into two distinct modes: interfacial and partial pullout. The reduced upper sheet thickness (∼685 μm) paves the way for crack propagation along the thickness direction, allowing for partial pullout failure to occur.